Adding to the knowledge of the TPACK framework: a case study of female identity in performance, education, and technology - Stephens-Himonides, Cynthia; Young, Margaret (Frontiers in Education, 2025)
IntroductionThe Technological Pedagogical Content Knowledge (TPACK) framework, developed by Mishra and Koehler, has served as a foundational model for aligning technology with pedagogy in educational research and practice. While TPACK emphasizes the integration of content, pedagogy, and technology in teacher knowledge, it often overlooks the role of teacher identity in shaping instructional decisions and technology use.MethodsThis study extends the TPACK framework by incorporating teacher identity as a critical component. Using a qualitative case study approach, we examined the experiences of an accomplished female music performer and educator. Data were collected through interviews and observations to explore how her musical background and personal identity intersect with her use of technology in piano teaching and performance.ResultsFindings reveal that the participant’s knowledge and identity significantly influenced her pedagogical choices and technology integration.DiscussionThese results suggest that teacher identity plays a pivotal role in how educators engage with technology. By extending the TPACK framework to include identity, this study provides a more holistic understanding of teacher knowledge and offers implications for teacher education by enabling teachers to remove obstacles to technology use and adoption.